NGARUH DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA INDUSTRI MEDIA PT. RIAU MEDIA TELEVISI (RTV) PEKANBARU - Leni November; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of work discipline and career development on employee performance partially and simultaneously. This study uses questionnaires as a means of collecting data distributed to 63 employees in Media Industries PT. Riau Media Television (Rtv) Pekanbaru. The data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 17.0 by performing validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis (R²) and hypothesis test with t test (partial) and F ( Simultaneous).The results showed that the results of the first hypothesis testing of work discipline on employee performance is(6,718) >(1,999), meaning that work discipline variables significantly affect employee performance. Both career development on employee performance is(7,954 >(1,999), meaning career development has a significant effect on employee performance. The result of F test of work discipline and career development on employee performance is(36,605) >(3,15), meaning work discipline and career development simultaneously have a significant effect on employee performance.Keywords: Work Discipline, Career Development, Employee Performance